The association between reading abilities and visual‐spatial attention in Hong Kong Chinese children. (25th March 2018) - Liu, Sisi; Liu, Duo; Pan, Zhihui; Xu, Zhengye
Abstract : A growing body of research suggests that visual‐spatial attention is important for reading achievement. However, few studies have been conducted in non‐alphabetic orthographies. This study extended the current research to reading development in Chinese, a logographic writing system known for its visual complexity. Eighty Hong Kong Chinese children were selected and divided into poor reader and typical reader groups, based on their performance on the measures of reading fluency, Chinese character reading, and reading comprehension. The poor and typical readers were matched on age and nonverbal intelligence. A Posner's spatial cueing task was adopted to measure the exogenous and endogenous orienting of visual‐spatial attention. Although the typical readers showed the cueing effect in the central cue condition (i.e., responses to targets following valid cues were faster than those to targets following invalid cues), the poor readers did not respond differently in valid and invalid conditions, suggesting an impairment of the endogenous orienting of attention. The two groups, however, showed a similar cueing effect in the peripheral cue condition, indicating intact exogenous orienting in the poor readers. These findings generally supported a link between the orienting of covert attention and Chinese reading, providing evidence for the attentional‐deficit theory of dyslexia.